Pengelolaan Diet dengan Kondisi Disfagia pada Pasien Stroke: Literature Review: Diet Management with Dysphagia Condition in Stroke Patients: A Literature Review - Gelora Mangalik; Anggita Raharjani Laurensia; Ayuningtyas Dian Ariestiningsih (Amerta Nutrition, 2023)
Background: Dysphagia is a condition often encountered in stroke patients and is a significant treatment challenge because it can increase the risk of malnutrition which can cause complications and increase the length of hospital stay. Objectives: This article aimed to determine diet management with dysphagia conditions in stroke patients through a review of the results of previous studies. Discussion: Diet management in stroke patients with dysphagia in the reviewed articles are nutrition screening, nutritional assessment, high-energy, high-protein feeding, energy restriction for weight loss, and provision of protein to maintain muscle mass. The dietary prescriptions were energy and protein adjustments, protein adjustments, fluid adjustments, nutritional supplements, food form adjustments, and feeding routes. The food preparation program uses a Dietary Well-being questionnaire assessment. This questionnaire consists of 21 questions which are divided into 4 categories, namely physical (5 questions), psychological (6 questions), emotional (5 questions), and social (5 questions). Modified Starch (MS) and Xanthan Gum (XG) thickeners use Volume-Viscosity Swallow Tests and Videofluoroscopic assessments to evaluate swallowing safety in stroke patients. Conclusions: Diet management in stroke patients can improve nutritional status, physical function, and dysphagia conditions and reduce the length of hospital stay. The food preparation program showed significant results on the Dietary Well-being questionnaire in the control group, especially in the psychological, emotional, and social categories. MS and XG thickeners improved swallowing safety in stroke patients.